Network Ripple Effects: How Twitter Deplatforming Flipped Authority Structure and Discourse of the Arizona Election Review Community - Michael Simeone; Steven R. Corman (SAGE Open)
Content moderation decisions can have variable impacts on the events and discourses they aim to regulate. This study analyzes Twitter data from before and after the removal of key Arizona Election Audit Twitter accounts in March of 2021. After collecting tweets that refer to the election audit in Arizona in this designated timeframe, a before/after comparison examines the structure of the networks, the volume of the participating population, and the themes of their discourse. Several significant changes are observed, including a drop in participation from accounts that were not deplatformed and a de-centralization of the Twitter network. Conspiracy theories remain in the discourse, but their themes become more diffuse, and their calls to action more abstract. Recruiting calls to join in on promoting and publicizing the audit mostly come to an end. The decision by Twitter to deplatform key election audit accounts appears to have greatly disrupted the hub structure at the center of the emergent network that formed as a response to the election audit. By intervening in the network, moderators successfully defused much of the Twitter-based participation in the Arizona Election Review of 2021. This instance demonstrates the efficacy of network-driven interventions in platform moderation, specifically for events or accounts that use social media to organize or encourage bad-faith attacks on civic instituions.